Forms of Representation in the Aristotelian Tradition Volume Three: Concept Formation - Thörnqvist, Christina Thomsen; Toivanen, Juhana (Brill, 2022)
The trilogy Forms of Representation in the Aristotelian Tradition investigates how Aristotle and his ancient and medieval successors understood the relation between the external world and the human mind. It gives an equal footing to the three most influential linguistic traditions - Greek, Latin, and Arabic - and offers insightful interpretations of historical theories of perception, dreaming, and thinking. This final volume focuses on intellectual operations and analyses some of the most exciting issues pertaining to the conceptual representation of the external world. The contributions cover the historical traditions and their impact on contemporary philosophy of mind.